A purchase intention model for foreign banks within Indonesia - Muchtar, Fatimah; Kingshott, Russel; Wong, David; Laksamana, Patria (Emerald Group Publishing Limited, 2012)
Purpose – This paper aims to present a conceptual model that highlights the complexities associated with foreign banks wishing to operate with the Indonesian marketplace. Design/methodology/approach – The paper is conceptual in nature and draws upon the marketing literature and theory to present a number of propositions. Findings – The paper melds key international marketing constructs by positing that Indonesian consumers using foreign banks yield utilitarian, hedonistic and symbolic benefits. These underlying consumer outcomes are modeled into variables likely to impact purchase intentions. Research limitations/implications – This paper represents the first attempt to conceptualize the many challenges facing foreign banks operating within an Indonesian setting. As Indonesia has a diverse range of cultures and values systems the model highlights the considerations associated with operating in such a diverse country. Practical implications – A number of important implications are presented for bank decision makers operating within Indonesia. Originality/value – A conceptual model is presented and the paper suggests a future research agenda applicable to both the Indonesian and wider banking context.